Young researcher takes home gold medals, Special Award at ENVEX 2010 - UMP, PNC
Fifteen young researchers from Universiti Malaysia Pahang (UMP) coveted three gold, two silver and three bronze medals at the Engineering Invention & Innovation Exhibition (ENVEX) 2010, which was jointly organized by Universiti Malaysia Perlis (UniMAP) and the Ministry of Science, Technology & Innovation (MOSTI), held at UniMAP’s Main Hall on April 2-4.